AN ECONOMIC STUDY OF THE EFFECTIVE FACTORS FOR BROILER PRODUCTION IN EASTERN REGIOM, CASE STUDY Al-AHSA GOVERNORATE. KINGDOM OF SAUDI ARABIA. - & Elsebaei, Mansour (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research was aimed to study the most important economic variables affecting of the production capacity of poultry meat in Al-Ahsa governorate by estimating the parameters of the production functions, the quantitative and value costs of the broiler farms,. The economic analysis method used a sample of 33 meat projects in the eastern region, representing 35.9% of the total number of projects in the Eastern Region and 92 projects till 2017. was divided into three categories, the first capacity (less than 150 thousand chickens), consisting of 16 projects representing 48.5% of the total sample farms and the second capacity (150 thousand to 300 thousand chickens), consisting of 10 projects representing 30.3% And the third (more than 300 thousand chickens) and consists of 7 projects representing 21.2% of the total sample farms, the results showed that the amount of feed and the number of chicks in the study sample ranked first and second in the total cost items of the first, second and third production capacity, representing about 63.6%, 64.8% and 63.1% (18.4% and 18.7%) with an average of about 63.9% and 18.4% respectively.